Resonant violence : affect, memory, and activism in post-genocide societies - Whigham, Kerry (New Brunswick : Rutgers University Press, 2022)
From the Holocaust in Europe to the military dictatorships of Latin America to the enduring violence of settler colonialism around the world, genocide has been a defining experience of far too many societies. In many cases, the damaging legacies of genocide lead to continued violence and social divisions for decades. In others, however, creative responses to this identity-based violence emerge from the grassroots, contributing to widespread social and political transformation. Resonant Violence explores both the enduring impacts of genocidal violence and the varied ways in which states and grassroots collectives respond to and transform this violence through memory practices and grassroots activism. By calling upon lessons from Germany, Poland, Argentina, and the Indigenous United States, Resonant Violence demonstrates how ordinary individuals come together to engage with a violent past to pave the way for a less violent future.
Frontmatter -- Contents -- Introduction: "The Abuse Lives in Our Blood" -- 1. Resonant Violence: The Felt Unfelt of Genocide and Its Aftermath -- 2. Building Memory: Practices of Memorialization in Post-Holocaust Berlin -- 3. Filling the Absence: Embodied Engagements with Former Sites of Atrocity -- 4. Embodied Justice: H.I.J.O.S., Practices of Trans-Action, and Biopoetics in Post-Dictatorship Argentina -- 5. Occupying Space, Amplifying Affect: The American Indian Occupation of Alcatraz Island -- Conclusion: Out of the Desert -- Acknowledgments -- Notes -- Bibliography -- Index -- About the Author
Description based upon print version of record.
JSTOR
Keywords: Genocide -- Social aspects; Genocide -- Political aspects; Violence; Collective memory; Violence; Violence; Mémoire collective; violence; POLITICAL SCIENCE / General; Collective memory; Genocide -- Political aspects; Violence; genocide, political violence, human right, human rights, memory, actiivist, activism, Argentina, Holocaust, Germany, merican Indian populations, American Indian, Cambodia, mass killing, Native American, twenty-first century, violence, economic disparity, inequality, institutional discrimination, Alcatraz Island, Alcatraz, grassroots activism, Poland, grassroot; Electronic books